Open Universities: Innovative Past, Challenging Present, and Prospective Future - Guri-Rosenblit, Sarah (International Review of Research in Open and Distributed Learning, 2019)
This article examines the innovative past of the large-scale, single-mode open universities that follow the model of the UK Open University (UKOU), analyzes the main challenges which they are currently facing in the digital era, and concludes with highlighting leading prospects for their future operation. The establishment of the UKOU in 1969 marked a new era in distance higher education. It gave distance education a new legitimacy and opened up new prospects for populations that for a variety of reasons were unable to attend a campus-based university. Many of the new open universities were heralded as a conspicuous development in higher education, with innovative features such as: open access, reaching out to part-time adult students, providing academic faculty the opportunity to work in teams to prepare study materials, modular credit accumulation, teaching huge numbers of students, and harnessing innovative technologies into their teaching/learning processes. In the last three decades, many of these innovative characteristics pioneered by open universities have been adopted by campus universities. This has eroded the unique status of open universities in many national jurisdictions. Furthermore, the emergence of digital technologies has challenged the underlying premises of the industrial model of many open universities, as well as their logistic operation. Present challenges facing open universities emerge from: blurred boundaries between distance and campus universities; the changing of initial target populations; the need to restructure the technological and logistic infrastructure of open universities; the changing roles of the academic faculty; and the growing competition for both students and funds. In order to find success and keep being relevant in the future, open universities should take into consideration: future target populations; the use of MOOCs and OER; support systems for both students and professors; collaboration with other higher education institutions; collaboration with the corporate and work worlds; and enhancing the academic status of open universities.